Integrated system for electrolyte recovery, product separation, and CO2 capture in CO2 reduction - Peng Wang; An Pei; Zhaoxi Chen; Peilin Sun; Chengyi Hu; Xue Wang; Nanfeng Zheng; Guangxu Chen (Nature Communications)
Abstract Challenges in CO2 capture, CO2 crossover, product separation, and electrolyte recovery hinder electrocatalytic CO2 reduction (CO2R). Here, we present an integrated electrochemical recovery and separation system (ERSS) with an ion separation module (ISM) between the anode and cathode of a water electrolysis system. During ERSS operation, protons from the anolyte flow through the anodic cation exchange membrane (CEM) into the ISM, acidifying the CO2R effluent electrolyte. Cations like K+ in the ISM flow through the cathodic CEM into the catholyte to balance the OH− ions from hydrogen evolution. ERSS recycles electrolyte-adsorbed CO2, recovers KOH with a 94.0% K+ yield, and achieves an 86.2% separation efficiency for CO2R products. The recovered KOH can capture CO2 from air or flue gas or be utilized as a CO2R electrolyte, closing the CO2 capture, conversion, and utilization loop. Compared to the conventional acid-base neutralization process, ERSS saves $119.76 per ton of KOH recovered and is applicable to other aqueous alkaline electrosynthesis reactions.